CONSTITUTING ISLAMIC SERVICE QUALITY AND ISLAMIC CUSTOMER RELATIONSHIP MANAGEMENT THROUGH CUSTOMER LOYALTY AND SATISFACTION - Rizky Ali Wardani; Budi Sukardi (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The findings found that Bank Syariah Indonesia Solo customers choose to use bank services that can meet the wants and needs of their customers. Therefore, the better the quality of services provided and the closer the relationship established, the higher the customer loyalty to Bank Syariah Indonesia Solo. This research aims to analyse the influence of Islamic Service Quality (ISQ), Islamic Customer Relationship Management (ICRM), and Customer Satisfaction (CS) on BSI Solo customer loyalty. The novelty of this research is to use the Islamic CRM variable to find out how much influence it has on BSI Solo customer loyalty and how satisfied BSI Solo customers are when Islamic CRM is appropriately implemented. The population in this research consisted of 170 samples. This research used quantitative methods, and the data was primary. The data analysed in this study used SmartPLS software with the analysis model carried out as PLS-SEM (Partial least-square structural equation model). The results of the research show that ISQ and ICRM have a significant effect on BSI Solo Customer Loyalty. ISQ and ICRM have a significant effect on BSI Solo Customer Satisfaction. Customer Satisfaction can mediate the relationship between ISQ and Customer Loyalty. Customer Satisfaction can mediate the relationship between ICRM and Customer Loyalty.